Obtaining a lipid extract from peach palm (Bactris gasipaes Kunth) epicarp. Quantification of carotenoid content and application as a food additive - Martínez-Girón, Jader; Osorio, Coralia; Ordoñez-Santos, Luis Eduardo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
The agro-industrial assessment of fruit by-products as food additives would allow compliance with Sustainable Development Goals. This research aimed at the homogenizer-assisted extraction of total carotenoids from peach palm (Bactris gasipaes) peel (epicarp) with sunflower oil. We also studied its application as a natural additive in white corn flour food. The response surface methodology and the rotational composite central design quantified the extraction process. The studied factors were extraction speed, temperature, time, and liquid-solid ratio. Total carotenoid content in the extract (336.06 µg/g dried epicarp) was optimized at 50°C, with 76 seconds, extraction speed of 19200 rpm, and liquid-solid ratio of 48.75 mL/g. The green extract obtained from homogenizer-assisted extraction constitutes a natural additive with agro-industrial potential for use in roasted corn cake, increasing carotenoid (30.60 µg/g of β-carotene), provitamin A (4.14 µg/g) and antioxidant activity (11.57 % DPPH). Highlights: Homogenizer-assisted extraction (HAE) is adequate for carotenoid extraction in peach palm epicarp. The lipid extract from the peach palm epicarp is a source of provitamin A. Lipid extract obtained is a natural additive with potential for use in corn griddle cakes.